Risk of incidence of hock burn and pododermatitis in broilers reared under commercial conditions - Jacob, Flavia Gerbi; Baracho, M. S.; Nääs, I. A.; Lima, N. S.D.; Salgado, D. D. [UNESP]; Souza, R. (FapUNIFESP (SciELO), 2016)
The most common lesions observed in commercial broiler farms are hock burns and pododermatitis, defined as necrotic lesions on the plantar surface of the footpads and in the hock of growing broilers, causing pain and compromising broiler welfare. The present study aimed at identifying the risks of hock burns and pododermatitis in broilers reared under commercial conditions on new or reused litter. Twenty-four 40-d-old broilers reared in two houses in a commercial broiler farm. The plantar surface of the footpads and the hocks of broiler were recorded using infrared thermal images. The incidence of hock burns in broilers reared on new litter was 0.72 times lower than those on reused litter. Broilers reared on new litter presented lower risk (0.75, RR<1) of presenting pododermatitis when compared to those reared on reused litter. When simulating the risk using a larger sample, the simulated risk of broilers presenting footpad and hock lesions when reared on new litter was 38% higher those reared on reused litter.
Keywords: Feet lesion; Litter; Poultry production